Knowledge, Adherence, and Barriers Related to Ventilator-Associated Pneumonia Prevention Among Critical Care Nurses in Baoshan, the People’s Republic of China - Jiang, Renjing; Sukonthasarn, Achara; Wangsrikhun, Suparat (Nursing Journal CMU, 2024)
Ventilator-associated pneumonia (VAP) is the most common complication found among patients who use mechanical ventilation as a life support measure. To improve the quality of nursing practice related to VAP prevention, baseline information regarding knowledge, adherence, and barriers related to VAP prevention among critical care nurses should be explored. This descriptive correlational design aimed to explore knowledge, adherence, and barriers to VAP prevention among critical care nurses in Baoshan City, the People’s Republic of China. The relationship between knowledge and adherence was also determined. Purposive sampling was used to recruit 142 critical care nurses from six hospitals in Baoshan City, Yunnan province, the People’s Republic of China. Measurement tools were composed of 1) the demographic data record form, 2) questionnaires related to knowledge towards prevention of VAP (QKVAP), and 3) the Questionnaire on VAP Prevention Compliance and Barriers (QVAPCB). The Chinese versions of these instruments were used. The internal consistency of the QKVAP using the KR-20 formula was .81, and the Cronbach’s alpha coefficients of the QVAPCB adherence and barrier parts were .91 and .87, respectively. Data were analyzed using descriptive statistics and Spearman’s rank-order correlation test. The results of this study were as follows: 1. The majority of participants (81.69%) had knowledge of VAP and VAP prevention at a fair level; 2. The majority of participants (95.07%) perceived adherence to VAP prevention at a sufficient level; 3. Knowledge was positively related to adherence to VAP prevention at a low level (r = .255, p < .001); 4. The top three barriers towards VAP prevention perceived by critical care nurses were forgetfulness to perform some evidence-based procedures (90.14%), staff shortages in the unit (82.39%), and noncompliance of patients in performing VAP prevention practice (59.15%). The study findings provide baseline information regarding critical care nurses’ knowledge and adherence, as well as the barriers to complying with VAP prevention. Further research should explore the factors influencing collaboration on and barriers to VAP prevention related to the use of ventilators in each ICU in order to have strategic plans to improve the VAP prevention.